2016
DOI: 10.7220/2335-8777.7.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Trečiasis sektorius ir socialinė gerovė; nevyriausybinių organizacijų vaidmuo gerovės valstybėje

Abstract: Kauno technologijos universitetas Šv. Ignaco Lojolos kolegija Santrauka. Straipsnyje aptariamas nevyriausybinių organizacijų (NVO) vaidmuo socialinės gerovės srityje joms vykdant veiklą ir teikiant paslaugas gerovės valstybėje. Pristatoma NVO samprata ir raida, jų klasifikacija. Atskleidžiama NVO dalyvavimo prasmė ir reikšmė socialinės gerovės užtikrinimo srityje, be kurios visuomenė lieka neįtrauki, padrika, kupina nerealizuotų lūkesčių ir uždarumo. Tokios valstybės negalima vadinti gerovės valstybe, garantuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…A significant contribution to the research on the evolution of local selfgovernment in Lithuania has been made by A. Lazauskienė as well. Concurrently with the aforementioned research focus on local self-governance, much emphasis was placed on the involvement of residents and the associations that bring them together 56 . Various scholars have examined the reforms implemented in local self-government and their strategies and tactics for empowerment.…”
Section: Local Government Research and Public Administration Research...mentioning
confidence: 99%
“…A significant contribution to the research on the evolution of local selfgovernment in Lithuania has been made by A. Lazauskienė as well. Concurrently with the aforementioned research focus on local self-governance, much emphasis was placed on the involvement of residents and the associations that bring them together 56 . Various scholars have examined the reforms implemented in local self-government and their strategies and tactics for empowerment.…”
Section: Local Government Research and Public Administration Research...mentioning
confidence: 99%
“…A civil society represents the moral and political method of organizing people in a community that demonstrates a phenomenon of autophagy, when people utilize themselves as a means of their survival, free choice and activity based on common values. According to Vorevičienė (2016), ensuring the community welfare and the empowerment to act independently in this area is a process of synergic interaction between the individual, the community, the organization and the broader range of social and political figures (Laverack, 2006;Ojhaa, et al, 2016). Therefore it is important to continue promoting the activities of NGOs (Lima, et al, 2016), communality and unity in all sectors and at all levels of government (as it is currently being done).…”
Section: Community Of a Regional Centrementioning
confidence: 99%
“…al., 2014; Orlova, 2014; Gruževskis, Šabanovas, 2015; Kaliatkaitė, Bulotaitė, 2014; Starkauskienė, 2011; Lu et al, 2013; Leliūgienė, 2012; Krutulienė, 2012; The Legatum prosperity index, 2016 et al), the authors of the article present the theoretical model of community welfare management (seeFigure 1). The theoretical model of community welfare management in the local community (adapted by Legatum Prosperity Index 2015;Gruževskis B., Orlov U. L., 2012, p.12, Šabanov S, 2015, Vorevičienė, J. 2016 …”
mentioning
confidence: 99%
“…An important factor in protecting children from violence is systems and measures that work effectively and ensure that children are protected from violence. Analyzing the issue of child protection revealed that researchers see child protection as part of a child-friendly environment (Vorevičienė, 2016). According to Falch-Eriksen, Backe-Hansen (2018), protecting the child's rights ensures a safe environment for the child to grow up and live in a family, and that is the task of relevant institutions.…”
mentioning
confidence: 99%